2016
DOI: 10.1038/srep32809
|View full text |Cite
|
Sign up to set email alerts
|

Paeoniflorin Potentiates the Inhibitory Effects of Erlotinib in Pancreatic Cancer Cell Lines by Reducing ErbB3 Phosphorylation

Abstract: Blockade of the epidermal growth factor receptor (EGFR) by EGFR tyrosine kinase inhibitors is insufficient for effective anti-tumor activity because the reactivation of the ErbB3 signaling pathway significantly contributes to activating the consequent phosphoinositide 3-kinase (PI3K)/Akt signaling pathway. Combinatorial therapies including ErbB3 targeting may ameliorate tumor responses to anti-EGFR therapies. In the present study, we found that in BxPC-3 and L3.6pl cells, which highly expressed the ErbB3 recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 41 publications
2
23
0
1
Order By: Relevance
“…Based on studies performed in recent years, it is found Paeoniflorin combined with gemcitabine inhibits pathways EGFR/ MAPK/ERK and ErbB3/PI3K/Akt, and increases proliferation of pancreatic cancer cell ErbB3. [46] Some other studies show that Paeoniflorin in concentration of 1000 lmol/l inhibits growth of pancreatic cancer cell through up-regulating expression of HRTA3 and promoting HTRA3 mediated apoptosis. [47] In 2018, Huang et al [48] found that Paeoniflorin inhibits proliferation of human pancreatic cancer cell Pane-1 and promotes apoptosis, for which the mechanism is probably that the pathway Caspase is activated.…”
Section: Lung Cancermentioning
confidence: 97%
See 2 more Smart Citations
“…Based on studies performed in recent years, it is found Paeoniflorin combined with gemcitabine inhibits pathways EGFR/ MAPK/ERK and ErbB3/PI3K/Akt, and increases proliferation of pancreatic cancer cell ErbB3. [46] Some other studies show that Paeoniflorin in concentration of 1000 lmol/l inhibits growth of pancreatic cancer cell through up-regulating expression of HRTA3 and promoting HTRA3 mediated apoptosis. [47] In 2018, Huang et al [48] found that Paeoniflorin inhibits proliferation of human pancreatic cancer cell Pane-1 and promotes apoptosis, for which the mechanism is probably that the pathway Caspase is activated.…”
Section: Lung Cancermentioning
confidence: 97%
“…found that Paeoniflorin exhibits potential anticancer effect through inhibiting pathways MMP‐9 and ERK while increasing apoptosis of pancreatic cancer cell panc‐1. Based on studies performed in recent years, it is found Paeoniflorin combined with gemcitabine inhibits pathways EGFR/MAPK/ERK and ErbB3/PI3K/Akt, and increases proliferation of pancreatic cancer cell ErbB3 . Some other studies show that Paeoniflorin in concentration of 1000 μmol/l inhibits growth of pancreatic cancer cell through up‐regulating expression of HRTA3 and promoting HTRA3 mediated apoptosis .…”
Section: Anticancer Activities Of Paeoniflorin and Its Potential Mechmentioning
confidence: 99%
See 1 more Smart Citation
“…Paeoniflorin, a pinane monoterpene glucoside, was first isolated from plants in the Ranunculaceae family in the 1960s (8). Recent studies have reported that paeoniflorin exhibits a number of pharmacological activities, including anti-cancer, anti-inflammation, anti-pulmonary fibrosis and anti-spasmodic effects (9)(10)(11). In nucleus pulposus cells, paeoniflorin serves an anti-apoptotic role via regulating B-cell lymphoma-2 family and caspase expression (12).…”
Section: Introductionmentioning
confidence: 99%
“…Today, there is interest in studying the therapeutic effects of Pae on different cancer types. In previous pharmacological investigations, Pae was confirmed to inhibit the growth of human pancreatic cancer, gastric carcinoma cells, colorectal carcinoma cells, and glioma cells (12)(13)(14)(15). A new study (16) recently reported the anti-proliferative properties of RPA extraction in treating BCa, both in vitro and in vivo.…”
mentioning
confidence: 92%